Classification of Euphemisms in Russian and Arabic (Outlooks and Aspects) - N. J., Hadi (Opción, 2019)
The article considers euphemism as a dynamic developed linguistic phenomenon in Arabic and Russian, the criteria for the classification of euphemistic units and the impact of linguistic and extralinguistic factors on this process via comparative qualitative research methods. As a result, the classification approach is also largely connected with linguistic and extralinguistic factors that surround euphemisms. Since euphemisms are considered to be part of the language, they live and develop like everything else in the language. In conclusion, euphemism is a developed updated and dynamic phenomenon in modern languages.